Wave propagation in helically orthotropic elastic cylindrical shells and lattices. (1st October 2019) - Sorokin, S.; Manconi, E.; Ledet, L.; Garziera, R.
Abstract: A use of orthotropic materials such as fibre-reinforced composites can introduce into vibro-acoustic performance of cylindrical structures effects that are not feasible when an isotropic material is used. In this paper, free and forced wave propagation in cylindrical structures with helically orthotropic material properties is analysed to demonstrate these effects. Two models, a thin cylindrical shell and a cylindrical beam lattice, are considered and two methods, an analytical method of the thin shell theory and a numerical Wave Finite Element method, are used. For both models, the symmetry break effect concerned with the location of dispersion curves is captured by means of these methods and explained. The influence of the helix angle and of the material parameters on the location of dispersion curves is investigated. The Green's matrix is formulated for rotating forces and the forcing problems are solved to highlight some unusual waveguide properties of the helically orthotropic cylindrical structures. The results are discussed in view of a possible application for control of energy flow in piping systems exposed to rotating excitation.